Analisis proses ekspor barang melalui jalur laut saat pandemi - Wiwin Yuniarti, Dwi (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
The Covid-19 pandemic has had a serious impact on all aspects of life, especially in the economic sector. This study aims to analyze the process of exporting goods by sea during a pandemic. This study uses qualitative research methods with data collection techniques literature study. The results showed that the process of exporting goods by sea during the pandemic was hampered due to restrictions on the number of cargoes that caused an increase in the price of a number of food commodities and the closure of a number of businesses.